The effect of helmets on motorcycle outcomes in a level I trauma center in Connecticut. (17th August 2016) - Wiznia, Daniel H.; Kim, Chang-Yeon; Dai, Feng; Goel, Alex; Leslie, Michael P.
ABSTRACT: Objective : The State of Connecticut has a partial motorcycle helmet law, which has been linked to one of the lowest helmet compliance rates in the Northeast. We examine the clinical and financial impact of low motorcycle helmet use in the State of Connecticut. Methods : A retrospective cohort study comparing the outcomes between helmeted and nonhelmeted motorcycle crash victims over a 12.5-year period, from July 2, 2002, to December 31, 2013. All patients who were admitted to the hospital after a motorcycle crash were included in the study. Patients were stratified into helmeted and nonhelmeted cohorts. Group differences were compared using t -test or Wilcoxon rank test for continuous variables and chi-square test for dichotomous outcomes. Regression models were created to evaluate predictors of helmet use, alcohol and drugs as confounding variables, and factors that influenced hospital costs. Results : The registry included 986 eligible patients. Of this group, 335 (34%) were helmeted and 651 (66%) were nonhelmeted. Overall, nonhelmeted patients had a worse clinical presentation, with lower Glasgow Coma Scale (GCS; P <.01), higher Injury Severity Score (ISS; P <.01), higher incidence of loss of consciousness (LOC; P <.01), longer intensive care unit (ICU; P <.01) admissions, and higher incidence of head ( P <.01) or face injuries ( P <.01). Nonhelmeted patients were also twice as more likely to die from their injuries ( P =.04, odds ratio [OR] = 1.89, 95% confidence interval [CI], 1.02–3.45). Financially, nonhelmeted patients incurred mean hospital costs of $18, 458, whereas helmeted patients incurred $14, 970 ( P =.18). ISS, GCS, and ICU length of stay were significantly correlated with increased hospital costs ( P <.01). Not using a helmet was a significant predictor of mortality ( P =.04) after adjusting for alcohol/drug use and age. Conclusions : Helmet use is associated with lower injury severity and increased survival after a motorcycle crash. These outcomes remained consistent even after controlling for age and alcohol and drug use. The medical and financial impact of Connecticut's partial helmet law should be carefully evaluated to petition for increased education and enforcement of helmet use.